2014
DOI: 10.1128/mcb.00193-14
|View full text |Cite
|
Sign up to set email alerts
|

H2A.Z-Dependent Regulation of Cohesin Dynamics on Chromosome Arms

Abstract: Structural maintenance of chromosomes (SMC) complexes and DNA topoisomerases are major determinants of chromosome structure and dynamics. The cohesin complex embraces sister chromatids throughout interphase, but during mitosis most cohesin is stripped from chromosome arms by early prophase, while the remaining cohesin at kinetochores is cleaved at anaphase. This two-step removal of cohesin is required for sister chromatids to separate. The cohesin-related Smc5/6 complex has been studied mostly as a determinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 69 publications
(108 reference statements)
0
19
0
Order By: Relevance
“…Cohesin levels at the centromeres are higher than on chromosome arms (Outwin et al , 2009; Tapia-Alveal et al , 2014b). As a cohesin regulator, the most obvious reason for the premature separation of centromeres was the absence of cohesin at this locus.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Cohesin levels at the centromeres are higher than on chromosome arms (Outwin et al , 2009; Tapia-Alveal et al , 2014b). As a cohesin regulator, the most obvious reason for the premature separation of centromeres was the absence of cohesin at this locus.…”
Section: Resultsmentioning
confidence: 93%
“…This occurs spontaneously in null mutants and in hypomorphs after DNA damage or replication stress (Verkade et al , 1999; Harvey et al , 2004). The mitotic failure is due to the postanaphase retention of cohesin on chromosome arms but not centromeres (Outwin et al , 2009; Tapia-Alveal et al , 2014a, b), that is, a failure of the prophase pathway. Although the mechanism leading to cohesin retention is not yet clear, the mitotic defects can be overcome by ectopic expression of separase (Outwin et al , 2009) and the loss of the histone variant H2A.Z (Tapia-Alveal et al , 2014b); both of these scenarios significantly lower arm cohesin levels, although H2A.Z levels have little to no effect on centromeric cohesin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, overexpression of the protease separase, which cleaves the kleisin subunit of cohesin, removes the arm cohesin complexes and suppresses the mitotic defects (Outwin, et al 2009). Second, in a screen for suppressors of the mitotic defects of smc6 mutants, we found that loss of the histone variant H2A.Z lowers arm cohesin levels by up to 50%, and this too allows mitosis to proceed (Tapia-Alveal, et al 2014). Importantly, in both scenarios the DNA damage and/or replication stress sensitivity of smc6 mutants is also suppressed, showing that the sensitivity is largely due to the mitotic defects.…”
Section: Coming Together In Mitosis To Allow Sisters To Come Apartmentioning
confidence: 99%
“…One hint that cohesin and Smc5/6 may have overlapping functions comes from the observation that most combinations of hypomorphic alleles of cohesin and Smc5/6 genes in S. pombe are either synthetic lethal or confer severe mitotic defects (Tapia-Alveal, et al 2014; Tapia-Alveal, et al 2011; Verkade, et al 1999). At least in the case of cohesin, the cyclic nature of its association with chromosomes means that a delicate balance of cohesin dynamics is critical; either too much or too little sister chromatid cohesion is incompatible with accurate chromosome segregation.…”
Section: Why Do Cells Have Both Cohesin and Smc5/6?mentioning
confidence: 99%